Pengaruh Pengunaan Media Sosial Terhadap Hasil Belajar Peserta Didik pada Pelajaran Pendididkan Pancasila dan Kewarganegaraan - Nisa Dwi Lestari; Asep Deni Normansyah; Darda Abdullah Siam (UNIVERSITAS SERAMBI MEKKAH, 2024)
The increase in the use of social media among students has increased by 30%. The use of learning media must also be changed according to the needs of students at that time. So conventional learning is no longer suitable for teachers to teach using textbooks alone. The use of social media is an alternative that teachers can use in providing learning materials to today's students. The aim of this research is to find out 1) what are the differences in student learning outcomes in Pancasila and Citizenship Education lessons after using YouTube social media compared to conventional learning media. 2) what is the effect of using YouTube social media on student learning outcomes in Pancasila and Citizenship Education lessons. 3) What is the response of students who learn by using YouTube? Using a non-equavalent control group design (quasi experimental) method. Subject class IIV Sumatra 40 Bandung Junior High School. The research results show the influence of the use of social media on students' use of social media on learning outcomes. Proven by independent tests until the t-test) obtained a significance value for both parties Sig (2-tailed) which is 0.000, <0.05 Ho is rejected and Ha is accepted as well as the result of tcount 4.424 > ttab 1.711 then Ho is rejected Ha is accepted .